A CASE OF HASHIMOTO’S THYROIDITIS IN A PATIENT WITH HEPATITIS C : THE EFFECT OF DIRECT-ACTING ANTIVIRAL (DAA) - Ismail, Hazwani; Chuan, Ng Oooi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The first discovery of a Hepatitis C Virus (HCV) association was found in mixed cryoglobulinemia. Multiple organs and systems were then affected including the thyroid. HCV may interfere with the functions and mechanisms of self-recognition of both the immune system and thyroid cells and may directly destroy thyroid tissue or mimic the structure of some components of the thyroid gland, thereby initiating autoimmune disease. Interferon (IFN) is a drug used in treating HCV, and studies have shown that IFN-induced thyroid autoimmunity can cause both hyperthyroidism and hypothyroidism. CASE A 45-year-old Malay male with underlying diabetes mellitus was admitted for difficulty of breathing and was diagnosed with Hashimoto’s thyroiditis with positive anti-TPO and anti-thyroglobulin antibodies complicated with pericardial effusion in 2018. His liver enzymes were abnormal and investigations revealed that he had HCV with liver cirrhosis secondary to heroin use in 2018. He was treated with DAA for 6 months in 2019. Repeated investigations showed that he achieved sustained virologic response (SVR). After SVR, his thyroxine dosage remained at 1.4 mcg/kg/day, ensuring compliance to medication timing. No antibodies were repeated. In terms of upper gastrointestinal bleeding, ascites, or bleeding tendency, the development of hypothyroidism did not seem to worsen liver cirrhosis. CONCLUSION The above case shows that DAA had no impact on thyroid autoimmunity in preexisting Hashimoto’s thyroiditis with HCV. Nonetheless, variations in the accuracy of the test techniques and other variables, such as iodine consumption and drugs, contribute to this discrepancy. Patients with HCV infection and autoimmune thyroid disease are influenced by a complex network of cytokines, chemokines, and their receptors. To determine how beneficial these mediators may be as thyroiditis prognostic indicators in the follow-up of HCV positive patients, more research with bigger populations are required.